PERSEPSI GURU TERHADAP PENERAPAN SISTEM INFORMASI MANAJEMEN BERBASIS DIGITAL DAN KURIKULUM BERBASIS CINTA DI SEKOLAH ISLAM - Asmiranda; Zainuri, Ahmad; Afriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers’ perceptions of the implementation of Digital-Based Management Information Systems (MIS) and the Love-Based Curriculum (LBC) at MAN 1 Palembang and to identify the factors influencing their implementation. This research employed a qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that teachers’ perceptions of MIS range from positive to skeptical, influenced by digital competence, infrastructure readiness, and training quality. In contrast, LBC is generally perceived positively due to its alignment with Islamic values, although challenges remain in terms of operationalization and consistency. Factors such as principal leadership, organizational culture, incentive systems, personal value alignment, and peer communication significantly influence perception and implementation success. These findings highlight that successful educational innovation requires a holistic strategy involving teacher capacity building, infrastructure support, and transformational leadership.